Efficiency of Currency Asset Classes - Safarzadeh, Mohammad R.; Ibrahimi Nazarian, Fatemeh; Molina, Ana Kristel C. (International Journal of Economics and Financial Issues, 2013)
Analyzing the risk and return for the S&P Currency Index Arbitrage and the Merk Absolute Return Currency Fund, this study intends to find whether currency asset classes are worthwhile investments. To determine where the efficient currency portfolios lie in the risk and return spectrum, this paper compares the two portfolios to fixed income and equity asset portfolios. The results lead to a baffling conclusion that, in general, the returns to low-risk currency asset portfolios are higher than the equity asset portfolios of same risk level. Keywords: Currency asset class; risk and return; fund allocation; efficient frontiers JEL Classifications: G15